Valuing local and dual-class IPOs in the Alternative Investment Market - Wahid, Abdul; Mumtaz, Muhammad Zubair; Mantell, Edmund (Estudios de Economía, 2020)
Initial Public Offerings are, by definition, not seasoned securities. They have not been subjected to valuation by the community of investors. It is often difficult or impossible to forecast their future cash flows because most do not have a long history of publicly disclosed financial information. Consequently, valuing IPOs in any market is more difficult than valuing seasoned equities. In this paper, we address the valuation of IPOs in the Alternative Investment Market, (hereafter the AIM.) The purpose of this study is to determine the observable factors that affect valuation in the AIM. We apply OLS, LASSO regression, and Extreme Bounds Analysis (EBA) techniques on historical accounting data to test our theory of valuation. The statistical sample consists of 2,185 IPOs issued on the AIM between 1995 and 2020. Our findings suggest that the market valuation of IPOs in the AIM is systematically related to a multiplicity of factors. These include earnings per share (EPS) in the after-market, operating cash follow per share, and the percentage of shares issued to the public. The findings of the study have a practical value for investors who are interested in buying IPOs in the AIM.